Dantrolene reduces CaMKIIδC-mediated atrial arrhythmias. Issue 7 (15th May 2020) - Pabel, Steffen; Mustroph, Julian; Stehle, Thea; Lebek, Simon; Dybkova, Nataliya; Keyser, Andreas; Rupprecht, Leopold; Wagner, Stefan; Neef, Stefan; Maier, Lars S; Sossalla, Samuel
Abstract: Aims: In atrial fibrillation (AF), an increased diastolic Ca 2+ leak from the sarcoplasmic reticulum (SR) mediated by calcium/calmodulin-dependent-protein-kinaseIIδC (CaMKII) can serve as a substrate for arrhythmia induction and persistence. Dantrolene has been shown to stabilize the cardiac ryanodine-receptor. This study investigated the effects of dantrolene on arrhythmogenesis in human and mouse atria with enhanced CaMKII activity. Methods and results: Human atrial cardiomyocytes (CMs) were isolated from patients with AF. To investigate CaMKII-mediated arrhythmogenesis, atrial CMs from mice overexpressing CaMKIIδC (TG) and the respective wildtype (WT) were studied using confocal microscopy (Fluo-4), patch-clamp technique, and in vivo atrial catheter-based burst stimulations. Dantrolene potently reduced Ca 2+ spark frequency (CaSpF) and diastolic SR Ca 2+ leak in AF CMs. Additional CaMKII inhibition did not further reduce CaSpF or leak compared to dantrolene alone. While the increased SR CaSpF and leak in TG mice were reduced by dantrolene, no effects could be detected in WT. Dantrolene also potently reduced the pathologically enhanced frequency of diastolic SR Ca 2+ waves in TG without having effects in WT. As an increased diastolic SR Ca 2+ release can induce a depolarizing transient inward current, we could demonstrate that the incidence of afterdepolarizations in TG, but not in WT, mice was significantly diminished in the presence of dantrolene. To translate these findings into an in vivo situation we could show that dantrolene strongly suppressed the inducibility of AF in vivo in TG mice. Conclusion: Dantrolene reduces CaMKII-mediated atrial arrhythmogenesis and may therefore constitute an interesting antiarrhythmic drug for treating patients with atrial arrhythmias driven by an enhanced CaMKII activity, such as AF.